A study on the puncture method of extrapedicular infiltration anesthesia applied during lumbar percutaneous vertebroplasty or percutaneous kyphoplasty. Issue 33 (August 2019) - Liu, Liehua; Wang, Haoming; Wang, Jiangang; Wang, Qian; Pu, Yu; Wang, Zili; Wu, Yuexiang; Xu, Yuan; Jin, Weidong
Abstract : Abstract: Extrapedicular infiltration anesthesia (EPIA) was reported for percutaneous vertebroplasty (PVP) and percutaneous kyphoplasty (PKP) and provided good local anesthetic effects. Because of differences in anatomical morphology at each lumbar level, the puncture method of EPIA is not uniform in each lumbar vertebrae. To accurately insert the anesthetic needle into the extrapedicular region, we researched the puncture method of EPIA at each lumbar level. We retrospectively analyzed computed tomography (CT) images in 230 patients with lumbar osteoporotic fractures, including 59 L1 fractures, 54 L2 fractures, 50 L3 fractures, 36 L4 fractures, and 31 L5 fractures. The puncture of EPIA was simulated in every fractured vertebrae through CT, and the skin puncture point, puncture direction, and puncture depth of the anesthetic needle were observed. These specific parameters were the distance from the skin puncture point to the superior border of the pedicle projection on the skin (distance AD), distance from the skin puncture point to the lateral border of the pedicle projection on the skin (distance BC), sagittal section angle (SSA), transverse section angle (TSA), and depth of EPIA. As the lumbar ordinal number increased, the SSA, distance AD, TSA, and distance BC for each lumbar level gradually increased, and the puncture depth gradually decreased, all these parameters showed significant differences among the 5 lumbar levels ( P  < .001). The recommended puncture methods for EPIA at each lumbar level, including distance AD, distance BC, SSA, and TSA, were as follows: in L1, 4 mm, 8 mm, 9° and 8°; in L2, 6 mm, 10 mm, 11° and 10°; in L3, 9 mm, 13 mm, 12° and 12°; in L4, 12 mm, 18 mm, 16° and 18°; and in L5, 20 mm, 26 mm, 24° and 24°. The depth of EPIA was 13 mm in L1-L3 and 11 mm in L4-L5. By confirming the skin puncture point and puncture direction of the anesthetic needle, from an anatomical perspective, EPIA is feasible for lumbar PVP (PKP).